Heavenly Bodies: Christina Mirabilis, Purgatorial Piety, and Care Between the Living and the Dead in the Hagiographies and Exempla of Thomas of Cantimpré - Sandy, Samantha Angelica (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2025)
This thesis focuses on how Dominican author Thomas of Cantimprée1201-1272) utilised the twice-resurrected Christina of St. Trond (1150-1224) to encourage devotion to the cult of saints and to promote different acts of purgatorial care. Christina stood at a crossroads of three different categories of the dead: the holy dead, the personal dead, and the unruly or dangerous dead (namely revenants and ghosts.) In examining Thomas's corpus within broader Liègeoise corpus, it is possible to better understand the roles of the holy women of Liège in shaping purgatorial piety, and how the new mendicant orders used this new form of piety to promote orthodoxy and to make monastic practices surrounding the care of the dead accessible to the laity during a period of doctrinal change and heterodoxical challenges to Church authority. The first chapter examines Thomas's depictions of Christina alongside Thomas's other saints and the other holy women of Liège, comparing Christina's spiritual progression to theirs. The second looks at Christina's purgatorial suffrages alongside accounts of the returning dead and purgatorial suffrages found in Thomas's exempla collection, the Bonum universale de apibus, as well as those found in other exempla collections, such as Jacques de Vitry's Sermones vulgares and the Dialogus miraculorum by Caesarius of Heisterbach. It also examines earlier depictions of care for the dead , such as the Cluniac poem, the Relatio metrica de duobus ducibus, which Thomas adapted for his most significant purgatorial suffrage. This thesis argues that Thomas's recommended acts of purgatorial care for the dead uniquely centred women as intercessors compared to his peers. It also argues that Christina shaped Thomas's ideals for purgatorial care, with Thomas adapting her weeping and vigils as accessible acts of care for the laity. Likewise, this thesis also compares Christina's vita to accounts of revenants found within William of Newburgh's Historia rerum Anglicarum and Walter Map's De nugis curialium, arguing that Christina subverted tropes of the dangerous revenant by bringing faith and redemption to her community, rather than pestilence or death: In examining Christina's life in this context, it is clear that her purgatorial ministry was deeply influential on Thomas's own career, and that she provided a new and accessible example of purgatorial care that Thomas would promote throughout his career.
APPROVED
Keywords: Death; Holy women; Mystics; Purgatorial piety; Thomas of Cantimpré; Christina of St. Trond; Dominicans; Hagiography; Purgatory; Jacques de Vitry; Women's studies; Latin; Exempla; Exemplum; Preaching; Grief; Mourning; Memory; Ghosts; Revenants; Demons; Undead; Dead; Suffrages; Liège